Potential Effect of Defatted Mealworm Hydrolysate on Muscle Protein Synthesis in C2C12 Cells and Rats - Seo-Hyun Choi; Tae-Hwan Jung; Kyoung-Sik Han (Applied Sciences)
(1) Background: the objective of this study was to examine the impact of defatted mealworm hydrolysate (DMH), formulated through protein hydrolysis, on muscle protein synthesis in C2C12 cells and rats; (2) Methods: C2C12 cells were treated with dexamethasone and DMH, and cell viability was quantified using the MTT assay. Twenty-four Sprague–Dawley rats were divided into three groups (control, DEX, and DEX + DMH) and treated for 8 weeks. The DEX and DEX + DMH groups were administered intraperitoneal injections of DEX at a concentration of 2.25 mg/kg over a 3-d period. The control and DEX groups were fed a control diet, whereas the DMH group had part of the protein composition of the control diet replaced with 3.5% of DMH. The impact of DMH on muscle protein synthesis was evaluated through the measurement of grip strength, gastrocnemius and tibialis anterior muscle weights, and the investigation of muscle protein synthesis and degradation factor mRNA expression utilising the real-time PCR method; (3) Results: in vitro experiments demonstrated that treatment with DMH at concentrations greater than 5 mg/mL markedly alleviated DEX-induced injury in C2C12 cells. In vivo experiments demonstrated that the mRNA expression levels of myogenin and myoblast determination proteins, which promote muscle protein synthesis, were significantly increased. Furthermore, rats fed DMH exhibited significantly enhanced grip strength and tibialis anterior weight; (4) Conclusions: these findings indicate that DMH may serve as a functional material capable of promoting muscle protein synthesis and that the utilization of proteolytic enzymes is advantageous for the effective utilization of mealworms.